TELEGRAM APPLICATIONS IN HISTORY LEARNING OF SMA NEGERI 2 KABANJAHE - Samsidar Tanjung; Zimmi Idaman Sitepu; Dina Ampera (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2022)
Learning limitations as a result of the covid-19 pandemic which requires distance learning or online learning (on the network) of history subjects based on the telegram application. This type of qualitative descriptive research aims to find out the events, facts and circumstances that occurred during the research by presenting what happened. This research was conducted to see the process and impact of the use of the telegram application on students' history learning at SMA Negeri 2 Kabanjahe. The data instrument in this study used observations, online interviews and instrument filling in class XI IPS 2 students as samples using google forms, as well as documentation. The method used to analyze the data is a qualitative technique. The result of the research is that by utilizing the telegram application in history learning for class XI students at SMA Negeri 2 Kabanjahe, it runs well with few obstacles on the network in the event of rain or power outages. This can be seen in the smooth learning process and the results of interviews with teachers and students who say there are no obstacles in the use of this telegram application as a medium in the history learning process, other than only network constraints in the event of rain or power outages. It can also be proven in the learning outcomes of students in the cognitive (knowledge) and psychomotor (skills) aspects that are good with the percentage of completeness reaching (64.7%) in the cognitive (knowledge) and (85.2%) psychomotor aspects (Skills).